HIGHER SCHOOL TEACHER’S PROFESSIONAL ACTIVITY: PROBLEM OF THE DESTRUCTION OF MEANING - Nataliya B. Moskvina (Высшее образование в России)
The submitted article is an attempt to comprehend the changes taking place with the university teacher during his/her career. Through reflection of her own state of mind, the author actualizes the problem of loss the professional activity’s meaning, alienation, and distortion of the professional values. Today the teacher’s activity is assessed only by the formal indices so it loses its meaning and essence. The result of hypercontrol and bureaucratization of this sphere is transformation of education into its imitation and one of the forms of social control.